Foreign Language Anxiety and Online Engagement During the COVID-19 Pandemic: a Comparison Between EMI and FMI University Students - García Castro, Verónica (2022)
Even though foreign language anxiety (FLA) has been studied in second language online learning more generally (Fondo & Jacobetty, 2019; Hurd, 2007; McNeil, 2014; Pichette, 2009), there is a lack of research on how FLA may afect university students’ academic engagement in online learning while studying through L2 English/French as a medium of instruction. The present study explored the efects of FLA on university students’ academic engagement with online learning during the COVID-19 pandemic. We surveyed 91 students studying through L2 English as a medium of instruction (L2 EMI) and 76 students studying through L2 French as a medium of instruction (L2 FMI) at universities in Costa Rica, using two adapted scales for measuring FLA and student engagement with online learning. Students were also asked what universities can do to support those who may sufer from FLA. We conducted two exploratory factor analyses on the scales used and multiple linear regressions to explore whether FLA afected students’ academic engagement with their online learning. Results of multiple linear regression analyses suggest that for students studying through L2 EMI, FLA positively infuenced their academic engagement with online learning and that coming from a rural area positively afected online engagement. For students studying through L2 FMI, FLA also had a signifcant positive infuence on their online engagement; however, coming from a rural area did not seem to signifcantly afect their online engagement. Additionally, students mentioned the need for more support, mainly via better organized learning contexts and psychological support. Overall, the results showed that university students experience